Territorial reform of areas with concentrated residence of minorities within decentralization policy under polyethnicity in Ukraine - Sierhiei Sakhanienko; Natalia Kolisnichenko; Oleg Dolzhenkov (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
The ethnic problem is of particular importance with neighboring states, which, as kin-states, seek to protect their diaspora in Ukraine. The purpose of the article is to analyze the results of territorial transformations in the areas of concentrared residence of ethnic minorities in Ukraine and their impact on the current ethno-political balance. To examine the territorial transformations in Ukraine various methods were used - statistical analysis and survey method to generalize the attitude of the population to territorial transformations in the areas of ethnic groups settlements; documentary method to analyse international and Ukraine documents on territorial forming; observation to reveal the minorities moods; content analysis of local governments documents etc. Being based on situational and comparative approaches, on statistical data, the peculiarities of the settlement and administrative structure in areas of concentrated residence of minorities in Ukraine were examined both before the reform of the territorial structure and after the corresponding changes in 2020. On the basis of a wide expert survey, the problematic issues of territorial reform in areas of concentrated residence of minorities were identified, and ways of their solution were proposed. After the analysis of the index of ethnic tolerance in areas of concentrated residence of minorities, a forecast was made about the stability of the territorial structure in areas of concentrated residence of minorities (Romanians and Moldovans), including the mixed (multi-ethnic) municipalities and raions (territorial districts).